EVIDENCE BASED CASE REPORT (EBCR) : PENGGUNAAN KASSA KERING STERIL PADA PERAWATAN TALI PUSAT TERHADAP BAYI BARU LAHIR (Politeknik Kesehatan Kemenkes Bandung, 2022)
Background: The removal of the umbilical cord needs to be considered properly because the ties are not strong enough, the ties can be removed and bleeding can occur in the umbilical cord that can harm the baby. Another danger to be afraid of is the danger of infection. Rope fasteners can use high-level disinfectant threads or plastic cable clamps. Purpose: to determine the effective of umbilical cord treatment methods that may affect the umbilical cord release time. Some methods that can be used in the treatment of umbilical cord detachment are sterile gauze and alcohol gauze. Method: In the implementation of this evidence based case report related to the treatment of umbilical cord wounds it was carried out well. Result: Conclusion: Mother was able to cooperate in the management of umbilical cord care using sterile gauze and alcohol gauze. Better results by applying sterile gauze.